2024
DOI: 10.1088/2752-5295/ad1f40
|View full text |Cite
|
Sign up to set email alerts
|

Warm Arctic–Cold Eurasia pattern driven by atmospheric blocking in models and observations

Zachary Kaufman,
Nicole Feldl,
Claudie Beaulieu

Abstract: In recent decades, Arctic-amplified warming and sea-ice loss coincided with a prolonged wintertime Eurasian cooling trend. This observed Warm Arctic-Cold Eurasia pattern has occasionally been attributed to sea-ice forced changes in the midlatitude atmospheric circulation, implying an anthropogenic cause. However, comprehensive climate change simulations do not produce Eurasian cooling, instead suggesting a role for unforced atmospheric variability. This study seeks to clarify the source of this model-observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…At the same time, parts of the Arctic have been warming ∼7x faster than the global mean over 1980-2022, which may implicate the role of internally driven sea-ice decline associated with atmospheric circulation anomalies (e.g., Day et al, 2012;Ding et al, 2014;England et al, 2019;Isaksen et al, 2022;Roach & Blanchard-Wrigglesworth, 2022;Svendsen et al, 2021). Furthermore, many studies have indicated the potential connection between Arctic warming and Northern Hemisphere continental cooling and the role of internal variability (Blackport et al, 2019;Cohen et al, 2014;Fyfe, 2019;Kaufman et al, 2024;Palmer, 2014). Our study suggests that internal variability has made an important contribution to observed Arctic warming, Eastern Pacific cooling, and Southern Ocean cooling over 1980-2022.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, parts of the Arctic have been warming ∼7x faster than the global mean over 1980-2022, which may implicate the role of internally driven sea-ice decline associated with atmospheric circulation anomalies (e.g., Day et al, 2012;Ding et al, 2014;England et al, 2019;Isaksen et al, 2022;Roach & Blanchard-Wrigglesworth, 2022;Svendsen et al, 2021). Furthermore, many studies have indicated the potential connection between Arctic warming and Northern Hemisphere continental cooling and the role of internal variability (Blackport et al, 2019;Cohen et al, 2014;Fyfe, 2019;Kaufman et al, 2024;Palmer, 2014). Our study suggests that internal variability has made an important contribution to observed Arctic warming, Eastern Pacific cooling, and Southern Ocean cooling over 1980-2022.…”
Section: Discussionmentioning
confidence: 99%